Pelatihan Penggunaan Alat Pemadam Api Ringan di Gedung Baru Inalum - Ruliyanta, Ruliyanta; Setyadi, Wismanto (Ikatan Ahli Informatika Indonesia, 2022)
This Community Service activity was carried out at the PT Indonesia Asahan Aluminum (Persero) Head Office Building, Batubara Regency, North Sumatra. This building has a green building concept. The green building concept requires workers to come from residents around the building. The building, which the Minister of SOEs inaugurated on January 6, 2021, is managed by local sons. The problem is that Inalum building management workers have no experience using LFE (Light Fire Extinguishers). To overcome these problems, training in the use of APAR is needed. This activity aims to provide training to Inalum building management employees. Participants The exercise was attended by 53 participants from the technicians, security guards, housekeeping, receptionists, gardeners, and gondola officers. Based on gender, the activity was attended by nine women and 44 men. Before the training, the level of understanding of officers about APAR was only 42%, while after the training, it increased to 70.75% or an increase of 28.68%.